السلطة التقديرية للإدارة في الرقابة على حق الفرد بالتخلي عن الجنسية دراسة مقارنة ( سورية ، مصر، لبنان، العراق، الكويت، الأردن) - الخابور, ساجر (Latakia University Journal - Economic and Legal Sciences Series, 2018)
على الرغم من استقرار مبدأ حق الفرد في التخلي عن جنسيته في مختلف التشريعات الوطنية كمبدأ من مبادئ تنظيم الجنسية و كحق نص عليه الإعلان العالمي لحقوق الإنسان، إلا أن هذه التشريعات تختلف في كيفية تنظيم حق الفرد بالتخلي عن جنسيته، وتحديد مدى رقابة الإدارة على ممارسة هذا الحق.وسنقوم في هذا البحث بدراسة حق التخلي في التشريعات العربية وكيفية تنظيمه من قبل المشرعين العرب، ومدى خضوعه للسلطة التقديرية للإدارة على أن نقوم بتعريف حق التخلي وتميزه عن المفاهيم المشابهة له في التمهيد، ثم نقوم بشرح أحكام التخلي وبيان سلطة الإدارة في التشريعات التي تعتبر التخلي حقاً مطلقاً للفرد في فصل أول، ثم نتحدث عن التخلي في تشريعات الدول التي تخضعه لسلطة الإدارة في فصل ثاني وبيان الحالات التي تسمح فيها بالتخلي وشروطه، ونختتم البحث بخلاصة نطرح فيها وجهة نظرنا عن كيفية تنظيم حق الفرد بالتخلي عن جنسيته، ومنح الإدارة سلطة الرقابة التي تحمي مصالح الدولة.Although the principle of individual's right to abandon his/her citizenship is established in the different national legislations as a citizenship regulating principle and as a right set out in the Universal Declaration of Human Rights, the legislations differ on how to regulate individual's right as for the abandonment of his/her citizenship and to define the administration's control on exercising of such right. In this research we will consider the right to abandon in the Arab legislations, the way it is regulated by the Arab legislators and how it is subjected to the administration's estimated authority; and we are going to define the right to abandon and discriminate it from the similar concepts in a preliminary chapter. We will then explain the rules of abandonment and demonstrate in a first chapter the administration's authority in legislations deeming the abandonment an individual's absolute right. Then we talk about the abandonment in legislations of the states making it subject to the administration's authority in a second chapter and demonstrate the cases it allows under which of the abondment and its conditions. We conclude the research with a summary mentioning our own point of view on how to regulate an individual's right to abandon his/her citizenship and grant administration the authority to control in order to protect state's interests.